DNA vaccine encoding peptide P10 against experimental paracoccidioidomycosis induces long-term protection in presence of regulatory T cells - Amorim, Juliana de (2013)
Paracoccidioidomycosis is a granulomatous systemic mycosis endemic in Brazil and other Latin America countries. A DNA vaccine encoding the inununoprotective peptide 10 (P10) significantly reduced the fungal burden in mice when given prior to or after intratracheal challenge with Paracoccidioides brasiliensis. Presently, the generation/expansion of CD4(+) CD44(hi) memory T cells as well as Foxp3(+) Treg cells in mice immunized with the DNA vaccine (pcDNA3-P10) before and after infection with P. brasiliensis was investigated. Memory CD4(+) CD44(hi) T cells simultaneously with Foxp3(+) Treg cells increased in the spleens and lungs of pcDNA3-P10 immunized mice on day 0, 30, 60 and 120 postinfection. Histopathology of the lung tissue showed minimal inflammation in immunized mice compared with the unimmunized group, suggesting a role for regulatory T cells in controlling the immunopathology. the DNA vaccine shows that the repeated immunization generates memory cells and regulatory T cells that replace the initially protective pro-inflammatory T cells conferring a long term protection while preserving the integrity of the infected tissue. (C) 2012 Institut Pasteur. Published by Elsevier Masson SAS. All rights reserved.